Anthropo-didactical approach to teacher-pupil interaction in teaching mathematics at elementary school - Sarrazy, Bernard; Chopin, Marie-Pierre (Scientia in educatione, 2013)
The paper focuses on interactions as one of the main constituents of a teacher’s didactical activity. The first part discusses characterization of the form of these interactions in three contrasting didactical contexts: the “devolving context”, “intermediary context” and “institutionalizing context”. The functions that they fulfill in a didactical system and their cognitive effects on pupils are studied. The second part deals with phatic interactions with the goal of showing how teachers proceed when trying to unite their educational mission with specific problems springing from various needs of different pupils.